Advocacy discourse in Surat An-Naml: A literary study - Abbas, Noora Obaid (Journal of Humanities & Social Sciences, 2020)
The research aims to identify the artistic representation in the advocacy discourse, especially the one that came from the Prophet’s guidance in Surat An-Naml, as it carries the sensory significance represented by the spiritual education of fidelity and the kinship. And the moral significance is in finding the right path to the righteous truth to the moral depiction of human values ​​of praise and thanksgiving to God, Lord of the Worlds. The study followed the analytical descriptive method which is based on mentioning the Qur’anic verse and showing its artistic pictorial features. The results revealed that imagining is the preferred tool to express the standard of moral criticism to highlight the realism of the spiritual and human values ​​of the Qur’anic stories in the light of Surat An-Naml. The study recommends the establishment of comprehensive research in the field of the propagandistic rhetorical miracles of the Holy Qur’an that deals with the verses from a rhetorical perspective of the miraculous claim and directing scholars to study its structures and clarify its secrets.